(untitled) (Nóema, 2024)
This essay examines Charles S. Pierce’s critique of nominalism against the background of the debate about natural kinds at the time of the first reception of Darwin’s Origin of Species. In the history of the so-called dispute over universals in Western philosophy, the phenomenon of species constancy has always been of central importance (since Plato). Darwin’s historicization of species was seen by some of Peirce’s contemporaries, including Chauncey Wright, as support for Mill’s nominalism. Peirce believed the opposite, that Darwin’s history of the origin of species supports realism about universals. This is so because for Darwin species arise independently of the human mind. Just as a history of science does not have to cast doubt on the reality of scientific disciplines, a history of species does not have to make their reality appear questionable. However, a concept of modifiable species is needed to understand this history. Peirce develops such a concept by understanding species, ahead of his time, as variable clusters.